2020
DOI: 10.1021/acsnano.0c04301
|View full text |Cite
|
Sign up to set email alerts
|

Multimode Interference of Bloch Surface Electromagnetic Waves

Abstract: Integrated photonics aims at on-chip controlling light in the micro-and nanoscale ranges utilizing the waveguide circuits, which include such basic elements as splitters, multiplexers, and phase shifters. Several photonic platforms, including the well-developed silicon-on-insulator and surfaceplasmon polaritons ones, operate well mostly in the IR region. However, operating in the visible region is challenging because of the drawbacks originating from absorption or sophisticated fabrication technology. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Proximity of PBG leads to high BSW leakage rate (see Section S1, Supporting Information), which helps us to study the BSW propagation using leakage radiation microscopy. [ 33,34 ] BSW can be excited in a wide range of spectrum from 450 to 650 nm, where effective refractive index nBSW$n_{\text{BSW}}$, which is equal to the ratio of BSW propagation constant kBSW$k_{\text{BSW}}$ and the radiation wavevector in vacuum k0$k_0$, decreases from 1.27 to 1. The BSW electric field distribution calculated by the transfer matrix method [ 35 ] is shown in Figure 1c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximity of PBG leads to high BSW leakage rate (see Section S1, Supporting Information), which helps us to study the BSW propagation using leakage radiation microscopy. [ 33,34 ] BSW can be excited in a wide range of spectrum from 450 to 650 nm, where effective refractive index nBSW$n_{\text{BSW}}$, which is equal to the ratio of BSW propagation constant kBSW$k_{\text{BSW}}$ and the radiation wavevector in vacuum k0$k_0$, decreases from 1.27 to 1. The BSW electric field distribution calculated by the transfer matrix method [ 35 ] is shown in Figure 1c.…”
Section: Resultsmentioning
confidence: 99%
“…BSW is a leaky mode meaning that part of the BSW energy leaks into the substrate during propagation. Intensity of leakage radiation is proportional to the BSW near‐field intensity, [ 34 ] while the leakage emission angle α$\alpha$ satisfies the phase‐matching condition nBSW=nsb$n_{\text{BSW}} = n_{\text{sb}}$sin(α$\alpha$), where nsb$n_{\text{sb}}$ is the refractive index of the substrate. Leakage radiation was collected with an objective lens.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported, through a rough experimental determination, an extinction coefficient smaller than 10 −2 cm −1 for the fundamental surface mode, [1] thus making optical surface waves relevant candidates for on-chip optical information transportation. Over the past 40 years, many studies have explored the possibilities offered by Bloch surface waves (BSWs), from the near-UV to mid-infrared wavelengths, [22][23][24][25][26][27][28][29][30] particularly for sensing applications. [31][32][33][34][35][36] Still, only very few works have discussed their propagation properties [37,38] and even fewer have made reports of experimentally measured propagation lengths.…”
Section: Introductionmentioning
confidence: 99%
“…The coupler size is scaled according to the size of the beam and is typically two to three beam diameters. We demonstrate the coupler for the Bloch surface wave (BSW) [8] platform that is all-dielectric counterpart to SPP one, but has the advantages of long propagation length [34] and ultrawide spectral range of operation (from UV [35] to mid-IR [36] ), making BSW applicable for integrated photonics, [10,[37][38][39] sensing, [40][41][42] and other fields. [43][44][45][46][47][48][49] Microprism couplers are printed on the surface of a photonic crystal using two-photon laser lithography [50] (TPL) capable of creating efficient in-plane [17] and out-of-plane microcouplers [19][20][21] operating on the mode-field matching principle.…”
Section: Introductionmentioning
confidence: 99%